Homogeneous Expansion of Human T-Regulatory Cells Via Tumor Necrosis Factor Receptor 2 - Okubo, Yoshiaki; Mera, Toshiyuki; Wang, Limei; Faustman, Denise L. (Scientific reports, 2013)
T-regulatory cells (T regs ) are a rare lymphocyte subtype that shows promise for treating infectious disease, allergy, graft-versus-host disease, autoimmunity and asthma. Clinical applications of T regs have not been fully realized because standard methods of expansion ex vivo produce heterogeneous progeny consisting of mixed populations of CD4 + T cells. Heterogeneous progeny are risky for human clinical trials and face significant regulatory hurdles. With the goal of producing homogeneous T regs , we developed a novel expansion protocol targeting tumor necrosis factor receptors (TNFR) on T regs . In in vitro studies, a TNFR2 agonist was found superior to standard methods in proliferating human T regs into a phenotypically homogeneous population consisting of 14 cell surface markers. The TNFR2 agonist-expanded T regs also were functionally superior in suppressing a key T reg target cell, cytotoxic T-lymphocytes. Targeting the TNFR2 receptor during ex vivo expansion is a new means for producing homogeneous and potent human T regs for clinical opportunities.